2009
DOI: 10.1523/jneurosci.5392-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Slow Conductances Could Underlie Intrinsic Phase-Maintaining Properties of Isolated Lobster (Panulirus interruptus) Pyloric Neurons

Abstract: The rhythmic pyloric network of the lobster stomatogastric system approximately maintains phase (that is, the burst durations and durations between the bursts of its neurons change proportionally) when network cycle period is altered by current injection into the network pacemaker (Hooper, 1997a,b). When isolated from the network and driven by rhythmic hyperpolarizing current pulses, the delay to firing after each pulse of at least one network neuron type [pyloric (PY)] varies in a phase-maintaining manner whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…4). Hooper et al (2009) found some of the same effects reported here, but did not examine changes in spike rate during long trains of inhibitory inputs, or look at the effects of changing DCI while holding period fixed. Thus our results are consistent with previous work, but reveal additional dimensions of the effects of rhythmic inhibition on excitability.…”
Section: Discussionmentioning
confidence: 51%
“…4). Hooper et al (2009) found some of the same effects reported here, but did not examine changes in spike rate during long trains of inhibitory inputs, or look at the effects of changing DCI while holding period fixed. Thus our results are consistent with previous work, but reveal additional dimensions of the effects of rhythmic inhibition on excitability.…”
Section: Discussionmentioning
confidence: 51%
“…The mechanisms that underlie the maintenance of phase over this range of frequencies have intrigued investigators, because membrane and synaptic currents have characteristic time constants, which would tend to create fixed delays, not constant phase (Hooper 1998; Manor et al 2003; Hooper et al 2009; Tang et al 2010), and it is thought that phase maintenance requires the interaction of multiple synaptic and intrinsic conductances (Manor et al 2003; Tang et al 2010). …”
Section: The Range Of Normal Pyloric Rhythmsmentioning
confidence: 99%
“…The variability in the number of spikes observed during the rebound could be related to the relative amount of T-type Ca 2+ currents or the expression of Cav3 channel subtypes in SPON neurons, as has been reported in postinhibitory rebound firing in deep cerebellar nuclei (Molineux et al, 2006). The fact that RDs trigger very few spikes in the SPON implies that additional ion conductances, such as voltage-gated K + channels (Kanold and Manis, 2001; Hooper et al, 2009) or Ca 2+ -activated K + channels (Kim and Trussell, 2007) that activate at more depolarized voltages, may influence the timing and/or the duration of the rebound response. In addition, geometrical variations in the size or the number of dendrites (Mainen and Sejnowski, 1996) or synaptic activity levels could influence the shape of the rebound response.…”
Section: Discussionmentioning
confidence: 99%